(untitled) («Наука и здравоохранение», 2026)
In this article gives the basic psychotherapeutic tactics at reactions of loss, described four tasks of sorrow, it’s forms and methods of decision, presented role of psychotherapeutics at reactions of loss, described universal steps, for recovery to normal life.